Analisis Daya Saing Ekspor Komoditas Tekstil Indonesia di Negara ASEAN - Dinda Fani Septiana; Diah Wahyuningsih (MediaTrend, 2020)
This research aims to analyze the competitiveness of export of textile commodities in ASEAN countries in 2010-2018. This research is a type of quantitative study. The analysis is conducted using the data panel which is the combined data of data cross section and time series published by the Central Statistic Agency (BPS), Worldbank, WITS. The method used in this study was Revealed Comparative Advantage (RCA), a data-panel regression. Based on the results of the analysis of RCA showed that the export of Indonesian textile commodities in ASEAN countries has a strong competitiveness in the country Malaysia, Singapore, Thailand, Vietnam because of the RCA value more than 1. In the results of a regression analysis of variable panel data on Indonesian exchange rate against the American dollar has a negative and insignificant influence on RCA, Gross Domestic Product (GDP) variable has a positive and significant influence on RCA, variable tenga work has a positive and insignificant influence on RCA, for Foreign Direct Investment (FDI) variables have a positive and significant influence on RCA.